The JWST early-release science program for direct observations of exoplanetary systems II: A 1 to 20 μm spectrum of the planetary-mass companion VHS 1256-1257 b - Miles, Brittany E.; Biller, Beth A.; Patapis, Polychronis; Worthen, Kadin; Rickman, Emily; Hoch, Kielan K. W.; Skemer, Andrew; Perrin, Marshall D.; Whiteford, Niall; Chen, Christine H.; Sargent, B.; Mukherjee, Sagnick; et al. (The astrophysical journal. Part 2, Letters, 2023)
We present the highest fidelity spectrum to date of a planetary-mass object. VHS 1256 b is a <20 M Jup widely separated (∼8″, a = 150 au), young, planetary-mass companion that shares photometric colors and spectroscopic features with the directly imaged exoplanets HR 8799c, d, and e. As an L-to-T transition object, VHS 1256 b exists along the region of the color-magnitude diagram where substellar atmospheres transition from cloudy to clear. We observed VHS 1256 b with JWST's NIRSpec IFU and MIRI MRS modes for coverage from 1 to 20 μm at resolutions of ∼1000-3700. Water, methane, carbon monoxide, carbon dioxide, sodium, and potassium are observed in several portions of the JWST spectrum based on comparisons from template brown dwarf spectra, molecular opacities, and atmospheric models. The spectral shape of VHS 1256 b is influenced by disequilibrium chemistry and clouds. We directly detect silicate clouds, the first such detection reported for a planetary-mass companion.
Gesehen am 07.09.2023